Dinardokanshones C–E, isonardoeudesmols A–D and nardoeudesmol D from Nardostachys jatamansi DC. (June 2018) - Wu, Hong-Hua; Deng, Xu; Zhang, Hu; Chen, Ying-Peng; Ying, Shu-Song; Wu, Yi-Jing; Liu, Yan-Ting; Zhu, Yan; Gao, Xiu-Mei; Xu, Yan-Tong; Li, Li
Abstract: Dinardokanshones C–E, three sesquiterpenoid dimers comprising an unusual nornardosinane-type sesquiterpenoid core and an aristolane-type sesquiterpenoid unit conjugated by an extra pyran or furan ring, together with monomeric sesquiterpenoids isonardoeudesmols A–D and nardoeudesmol D, were isolated from the underground parts of Nardostachys jatamansi DC. Structures of the eight compounds were elucidated by analysis of the extensive spectroscopic data, and their absolute configurations were established by analysis of NOESY and X-ray diffraction data, combined with computational electronic circular dichroism (ECD) calculations. The results of SERT activity assay revealed that isonardoeudesmol D and nardoeudesmol D significantly inhibited SERT activity, while dinardokanshones D–E and isonardoeudesmols B–C significantly enhanced SERT activity, among which dinardokanshone D exhibited the strongest effect. Graphical abstract: Previously undescribed dinardokanshones C–E, isonardoeudesmols A–D and nardoeudesmol D, were isolated from the underground parts of Nardostachys jatamansi DC., and their SERT activities were reported. Highlights: Hexacyclic sesquiterpenoid dimers with unusual skeletons were isolated from Nardostachys jatamansi DC. Biosynthetic pathways of the previously undescribed dinardokanshones were proposed. SERT activities of dinardokanshones, isonardoeudesmols and nardoeudesmol D were reported.